Işıklı gölü (Denizli)'nde yayılış gösteren bazı sucul makrofitlerin toksik metal iyonlarına karşı (Cu++, Cd++ ve Ni++) biyoakümülasyon yeterliliklerinin araştırılması - Zeytünlüoğlu, Ali (Pamukkale Üniversitesi, 2004)
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz. m In this study, the bioaccumulation sufficiency of plants Lemna trisulca, Ceratophyllum submersion, Groenlandia densa ve Apium nodiflorum, which are distributed in aquatic ecosystems against toxic metal ions was tested. In the laboratory condition, plants were exposed to prepared stock solution of copper, cadmium, and nickel metals with 1.0, 3.0, 5.0, and 7.0 ppm concentration metal solutions in certain periods (24, 48, 72, and 96 hours) and changing amount of accumulation of plants in depending on time and concentration was measured by atomic absorption spectrometer. As a result of data evaluation, it was found out that cadmium, cupper, and nickel materials were accumulated in different ratio by four aquatic plants in depending on time and concentration and the most accumulation for all metals was materialized on the fourth day. It is concluded that plants, submerged, accumulate more ratios of heavy metals in comparison with plants, free-floating and emergent; furthermore, rooted plants accumulate more ratios of heavy metals in comparison with rootedless plants. When the abilities of the heavy metal accumulation of the plants were compared, it is found that plant of G. densa accumulates the maximum ratio of heavy metals. Key Words: Heavy metals, Water pollution, Bioaccumulation, Işıklı lake, and Macrophytes Ali ZEYTÜNLÜO?LU II Bu çalışmada; toksik metal iyonlarına karşı (Cd, Cu ve Ni), sucul ekosistemlerde yayılış gösteren Lemna trisulca, Ceratophyllum submersum, Groenlandia densa ve Apium nodiflorum bitkilerinin, değişen zamana ve konsantrasyona bağlı biyoakümülasyon yeterlilikleri test edilmiştir. Bitkiler laboratuvar şartlarında bakır, kadmiyum ve nikel metallerinin stok solüsyonlarından (1000 ppm) 1.0, 3.0, 5.0 ve 7.0 ppm konsantrasyonlarında hazırlanan metal çözeltileriyle, belli zaman periyodlarında (24, 48, 72 ve ...